Ligand-to-diimine/metal-to-diimine charge-transfer excited states of [Re(NCS)(CO)3(alpha-diimine)] (alpha-diimine = 2,2'-bipyridine, di-iPr-N,N-1,4-diazabutadiene). A spectroscopic and computational study - Blanco Rodríguez, Ana Maria; Gabrielsson, Anders; Motevalli, Majid; Matousek, Pavel; Towrie, Michael; Sebera, Jakub; Zális, Stanislav; Vlcek, Jr, Antonín (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2005)
Two new complexes fac-[Re(NCS)(CO)3(N,N)] (N,N = 2,2'-bipyridine (bpy), di-iPr-N,N-1,4-diazabutadiene (iPr-DAB)) were synthesized and their molecular structures determined by X-ray diffraction. UV-vis absorption, resonance Raman, emission, and picosecond time-resolved IR spectra were measured experimentally and calculated with TD-DFT. A good agreement between experimental and calculated ground- and excited-state spectra is obtained, but only if the solvent (MeCN) is included into calculations and excited state structures are fully optimized at the TD-DFT level. The lowest excited states of the bpy and iPr-DAB complexes are assigned by TD-DFT as 3aA' by comparison of calculated and experimental IR spectra. Excited-state lifetimes of 23 ns and ca. 625 ps were determined for the bpy and DAB complex, respectively, in a fluid solution at room temperature. Biexponential emission decay (1.3, 2.7 micros) observed for [Re(NCS)(CO)3(bpy)] in a 77 K glass indicates the presence of two unequilibrated emissive states. Low-lying electronic transitions and excited states of both complexes have a mixed NCS --> N,N ligand-to-ligand and Re --> N,N metal-to-ligand charge-transfer character (LLCT/MLCT). It originates in mixing between Re d(pi) and NCS pi characters in high-lying occupied MOs. Experimentally, the LLCT/MLCT mixing in the lowest excited state is manifested by shifting the nu(CO) and nu(NC) IR bands to higher and lower wavenumbers, respectively, upon excitation. Resonant enhancement of both nu(CO) and nu(NC) Raman bands indicates that the same LLCT/MLCT character mixing occurs in the lowest allowed electronic transition.